Handbook of developmental disabilities - Odom, Samuel L. (Guilford Press, 2007)
Analyzes what works in intervening with diverse children and families, from infancy through the school years and the transition to adulthood. This book reviews knowledge about developmental disabilities such as: neuroscientific and genetic foundations; the impact on health, learning, and behavior; and, effective educational and clinical practices.